Generation one - Lore, Pittacus (New York: Harper, an imprint of HarperCollinsPublishers, 2018)
"It has been one year since the breathtaking events of United as One -- and our world will never be the same. The invasion of Earth was thwarted by our alien allies known as the Garde. But in order to do so, they unleashed their Loric energy and it spread throughout the globe. Now human teenagers have begun to develop incredible abilities -- Legacies of their own. As the world tries to figure out how best to deal with the emergence of these powerful and potentially dangerous individuals, the Garde have come up with their own solution. They've created an academy where they can train this new generation to control their powers and hopefully one day help mankind...but that day may come sooner than any of them ever imagined."--
Keywords: Good vs evil -- Juvenile fiction; Good vs evil; Teenagers -- Juvenile fiction; High school students -- Juvenile fiction; Superheroes -- Juvenile fiction; Ability -- Juvenile fiction; Extraterrestrial beings -- Juvenile fiction; Human-alien encounters -- Juvenile fiction; Science fiction; Extraterrestrial beings -- Fiction; Extraterrestrial beings -- Fiction; Ability; Extraterrestrial beings; High school students; Human-alien encounters; Superheroes; Teenagers; Teenagers -- Fiction; Ability -- Fiction; School stories; Young adult fiction; Science fiction; Fiction; Juvenile works; Print books; Science fiction; Young adult works; Science fiction; Science fiction